Structural Engineering of Activated Carbon Fibers Derived from Cigarette Butts for Fast Oily Materials Adsorption - Zahra Ranjkesh; Fatemeh sadat Mousavi; Komeil Nasouri (محیط زیست و مهندسی آب, 2023)
In recent years, an effective recycling process from smoked cigarette butts is the main challenge for decreasing the worldwide environmental pollution. Therefore, low-cost activated carbon fibers (ACFs) are synthesized by a carbonization/ activation process derived from smoked cigarette filters, in which potassium hydroxide (KOH) acts as the chemical activation agent. The KOH-treated filters were added to a tube oven and heated at various rates and held at 800 °C for 1 h under a nitrogen atmosphere. The effects of various synthesis procedures on surface morphology, microstructure, and porosity of the synthesized ACFs were investigated. The surface morphology and microstructural analysis of ACFs displayed that the porous spots and oxygen-containing groups (COOH, –OH, and C=O) are formed on the surfaces of fibers. The obtained results displayed that the synthesized ACFs have developed porous structures with fibrous shapes. The ACFs with maximum carbon yield, surface area, and total pore volume of 29.41 %, 855 m2/g, and 0.7431 cm3/g were synthesized at a KOH concentration of 10 g/l, a heating rate of 2 °C/min, and carbonization temperature of 800 °C. This study presented an engineering process for the production of ACFs through recycling smoked cigarette butts with chemical activation protocol.